Las condiciones laborales y su relación con el incremento de la productividad - Suárez Caicedo, Angélica de el Cisne (2021)
The study emphasizes the importance of working conditions and their relationship with productivity in the clergy sector. Health and the quality of work life can be affected by this Burnout syndrome as a result of suffering from chronic stress, at the same time it involves negative attitudes and unpleasant emotions in the work environment and in its environment. The workload, working conditions, among others, are factors that affect the well-being of the Clerics, making them vulnerable. Increasing productivity becomes an essential objective for every organization. The objective is to know in what working and productive conditions are clerics, using three instruments: The MBI, interview and sociodemographic questionnaire. Through the working conditions, work climate and productivity, it has been determined that the clergy are suffering from the Burnout syndrome due to the stress that they live in each of their parishes……….